A room temperature CO2 line list with ab initio computed intensities. (July 2016) - Zak, Emil; Tennyson, Jonathan; Polyansky, Oleg L.; Lodi, Lorenzo; Zobov, Nikolay F.; Tashkun, Sergey A.; Perevalov, Valery I.
Abstract: Atmospheric carbon dioxide concentrations are being closely monitored by remote sensing experiments which rely on knowing line intensities with an uncertainty of 0.5% or better. We report a theoretical study providing rotation–vibration line intensities substantially within the required accuracy based on the use of a highly accurate ab initio dipole moment surface (DMS). The theoretical model developed is used to compute CO2 intensities with uncertainty estimates informed by cross comparing line lists calculated using pairs of potential energy surfaces (PES) and DMS׳s of similar high quality. This yields lines sensitivities which are utilized in reliability analysis of our results. The final outcome is compared to recent accurate measurements as well as the HITRAN2012 database. Transition frequencies are obtained from effective Hamiltonian calculations to produce a comprehensive line list covering all 12 C 16 O2 transitions below 8000 cm − 1 and stronger than 10 − 30 cm /molecule at T = 296 K . Abstract : Highlights: An ab initio dipole surface is used to compute CO2 line intensities. Multiple line lists are used to check the stability of the calculations. A comprehensive line list is given in HITRAN format.